2016
DOI: 10.6004/jnccn.2016.0037
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Breast Cancer Version 1.2016, NCCN Clinical Practice Guidelines in Oncology

Abstract: Breast cancer is the most common malignancy in women in the United States and is second only to lung cancer as a cause of cancer death. The overall management of breast cancer includes the treatment of local disease with surgery, radiation therapy, or both, and the treatment of systemic disease with cytotoxic chemotherapy, endocrine therapy, biologic therapy, or combinations of these. This article outlines the NCCN Guidelines specific to breast cancer that is locoregional (restricted to one region of the body)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
246
1
17

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(279 citation statements)
references
References 87 publications
8
246
1
17
Order By: Relevance
“…For some cancers, such as breast cancer and colorectal cancer, the association between the greater number of harvested LN and favorable survival has been established; thus, minimal number of dissected LNs is recommended for accurate staging (18,19). Although the current NCCN guidelines for NSCLC don't recommend the minimal number of harvests LN, Dr. Liang et al analyzed the US SEER data and a Chinese multi-institutional registry and found that a greater number of harvested LN was associated with more-accurate node staging and better long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…For some cancers, such as breast cancer and colorectal cancer, the association between the greater number of harvested LN and favorable survival has been established; thus, minimal number of dissected LNs is recommended for accurate staging (18,19). Although the current NCCN guidelines for NSCLC don't recommend the minimal number of harvests LN, Dr. Liang et al analyzed the US SEER data and a Chinese multi-institutional registry and found that a greater number of harvested LN was associated with more-accurate node staging and better long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year results of the trial changed practice, albeit modestly [18] and the National Comprehensive Cancer Network guidelines [19] allow BCS±WBRT in women ≥70 years with clinical stage 1 hormone receptor positive EBC. The PRIME 2 trial [20] randomized 1326 women ≥65 years with T1, T2 (≤3cm), pN0 tumours to 5-year adjuvant endocrine therapy (ET) ±WBRT.…”
Section: Role Of Radiotherapy (Rt) After Breast Conservative Surgmentioning
confidence: 99%
“…[6,7] International guidelines confirm that 1 year of trastuzumab remains the standard of care as part of an adjuvant therapy regimen for patients with HER2-positive early breast cancer. [8][9][10] We note the following specific issues in relation to the commentary: 1. Parameters used in the number needed to treat (NNT) calculation:…”
Section: Cost Considerations In Determining the Affordability Of Adjumentioning
confidence: 99%